PENGEMBANGAN MESIN DOWEL 3 IN 1 PEMBUAT PASAK KAYU UNTUK PEMBANGUNAN PERAHU NELAYAN DI WILAYAH PESISIR MADURA - Iswidodo, Windra; Fikri, Mohammad Anas; Permata, Tristiandinda; Abdullah, Mohammad (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
The coastal area of ​​Madura has many fishing boats or fishing vessels of various types and sizes. The construction of traditional ships is carried out by groups of workers or traditional shipyards which are not permanent, technological readiness is still minimal, and the workforce is very limited. Especially in traditional shipyards in the coastal area of ​​Madura or throughout Indonesia's coastal areas, which still rely on skills from generation to generation, so it is difficult to achieve the ship size desired by the customer, even the deviation of the size in tons can reach 25 percent. This situation shows the weakness of the technology applied in the traditional shipbuilding industry. Therefore, the technology of dowel making machine for making wooden dowels is carried out 3 in 1 with the function of shaving wood, cutting wood as desired and sharpening pegs or wood. All work is done in one machine which can be done automatically by setting the desired peg size and running with a microcontroller system. Tests have been carried out on a 3 in 1 dowel machine using 2 motors, the average time is equal to or more than 1 minute/1 piece of peg. Testing the tool using 1 motor obtained an average time of less than 30 seconds to produce 1 wooden peg.